Perovskite Nanomaterials: 0D–2D and 1D–2D Semiconductor Hybrids Composed of All Inorganic Perovskite Nanocrystals and Single‐Layer Graphene with Improved Light Harvesting (Part. Part. Syst. Charact. 2/2018). (21st February 2018) - Chen, Jia‐Shiang; Doane, Tennyson L.; Li, Mingxing; Zang, Huidong; Maye, Mathew M.; Cotlet, Mircea
Abstract : In article No.1700310, Mathew M. Maye, Mircea Cotlet and co‐workeres demonstrate the doping of poorly absorbing, highly conductive single‐layer graphene with perovskite nanocrystals and nanowires for next‐generation photodetectors. The method provides a simple and efficient path to obtain hybrids with increased light‐harvesting properties and improved exciton production.